2022
DOI: 10.54393/pjhs.v3i07.425
|View full text |Cite|
|
Sign up to set email alerts
|

Retraction Note: Prevalence of Musculoskeletal Pain Due to Smart Phone Usage Among High School Students-A Crosssectional Study

Abstract: In the past decade, mobile phone usage rates have increased and there have been concerns that the overuse of smart phones may contribute to various musculoskeletal (MSK) problems primarily in neck and shoulder region. The most reported complaint is pain that can be seen in many parts of the body, especially in neck. Objective: To check the prevalence of cervical pain and its association with smart phone usage among high school students. Methods: It was an observational cross-sectional study in which non-probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Results of the present study indicated that age, grade, time spent daily on media/technology usage, and using technology at bedtime were not significant predictors of musculoskeletal pain. As stated by Khalid A et al [ 37 ], there was no significant relationship between age and the modified neck and shoulder disability index, nor was there any relationship between gender and the modified neck and shoulder disability index. Additionally, a previous study conducted on 120 nursing students at a university in Riyadh, the capital city of Saudi Arabia, found no significant relationship between neck pain and either age or gender [ 22 ].…”
Section: Discussionmentioning
confidence: 75%
“…Results of the present study indicated that age, grade, time spent daily on media/technology usage, and using technology at bedtime were not significant predictors of musculoskeletal pain. As stated by Khalid A et al [ 37 ], there was no significant relationship between age and the modified neck and shoulder disability index, nor was there any relationship between gender and the modified neck and shoulder disability index. Additionally, a previous study conducted on 120 nursing students at a university in Riyadh, the capital city of Saudi Arabia, found no significant relationship between neck pain and either age or gender [ 22 ].…”
Section: Discussionmentioning
confidence: 75%
“…According to the report of Sirajudeen et al [ 11 ], female gender and participants with increased weight were significantly associated with the occurrence of musculoskeletal disorders. However, in a study by Khaled et al [ 18 ], they found no significant association between disability scores in terms of gender and age. Our study also observed this, wherein PRWHE scores have no significant association with gender, nationality, education, occupation, smoking status, or the dominant hand (p>0.05).…”
Section: Discussionmentioning
confidence: 95%